2020
DOI: 10.3390/antiox9040324
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of Glioprotective Intracellular Signaling Pathways in Primary Optic Nerve Head Astrocytes after Treatment with Different Classes of Antioxidants

Abstract: Optic nerve head astrocytes are the specialized glia cells that provide structural and trophic support to the optic nerve head. In response to cellular injury, optic nerve head astrocytes undergo reactive astrocytosis, the process of cellular activation associated with cytoskeletal remodeling, increases in the rate of proliferation and motility, and the generation of Reactive Oxygen Species. Antioxidant intervention has previously been proposed as a therapeutic approach for glaucomatous optic neuropathy, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…Intriguingly, Xanthohumolencapsulating PLGA NP had a much larger effect on 8-OHdG labeling in the cornea, reducing density of immunolabel by ~50% (Figure 9), compared with an ~25% reduction elicited by Mn-TM-2-PyP [17]. Given that the antioxidant potential of Mn-TM-2-PyP is significantly greater than that of Xanthohumol ( [17,31]), this finding may suggest that Xanthohumol-encapsulating PLGA NP are not only able to be retained at the ocular surface for a prolonged period of time despite their negative surface charge, but also achieve sustained activation of the endogenous antioxidant system.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Intriguingly, Xanthohumolencapsulating PLGA NP had a much larger effect on 8-OHdG labeling in the cornea, reducing density of immunolabel by ~50% (Figure 9), compared with an ~25% reduction elicited by Mn-TM-2-PyP [17]. Given that the antioxidant potential of Mn-TM-2-PyP is significantly greater than that of Xanthohumol ( [17,31]), this finding may suggest that Xanthohumol-encapsulating PLGA NP are not only able to be retained at the ocular surface for a prolonged period of time despite their negative surface charge, but also achieve sustained activation of the endogenous antioxidant system.…”
Section: Discussionmentioning
confidence: 94%
“…Human corneal epithelial cells (HCE-T; RIKEN BioResource Research Center, Tsukuba, Japan) were cultured as described by us previously [17,[31][32][33]. Cultures of passages 79 to 95, were used for experiments.…”
Section: Cell Culturementioning
confidence: 99%
“…A variety of homeostatic and prosurvival astrocyte activities have recently been described, strengthening the concept of key glioprotective central nervous system mechanisms ( 2 , 52 , 53 , 54 , 55 ). In previous work, we established that the astrocyte secretome contains potent neuroprotective factors that ameliorate metabolic and excitotoxic neuronal injury in in vitro and in vivo models ( 12 ).…”
Section: Discussionmentioning
confidence: 97%
“…In fact, many studies have demonstrated that RSV can reduce ROS in glaucoma models (in vitro and in vivo) through several pathways ( Figure 4 ) [ 114 , 115 , 116 ]. This downregulation of ROS could be due to the modulation of the endogenous antioxidant system [ 117 ], such as induction of nuclear factor erythroid-2-related factor 2 (Nrf2) translocation into the nucleus, where it binds to antioxidant response elements (ARE). This latter leads to the production of heme oxygenase-1 (HO-1), an anti-oxidant enzyme [ 117 , 118 ].…”
Section: Glaucoma and Rsv Actionmentioning
confidence: 99%